Assessment of Toxic Heavy Metal Concentration and their Changes in Zayande-rood River, Isfahan, Iran - Tabatabaei, Javad; Hassanzadeh, Nasrin; Alizade, Atefe (International Journal of Bio-resource and Stress Management, 2010)
Zayande-rood is one of the most important rivers flowing in the central part of Iran. The river water is used for drinking, industrial and agricultural purposes. However, industries mushroomed on the river bank, viz. steel factory (zovb-e-ahan), power plants, refinery and petrochemical complexes and mining activities drain wastewater into the river. In this study, the concentrations of heavy metals (Cd, Cu, Mn, Fe, Zn, Pb, Ni, Cr, V, Mo and As) in the Zayande-rood river were determined. Samples were collected from 12 stations along the river from Baghbahadoran to Isfahan in autumn 2009. Heavy meta l concentrations were obtained after acid digestion and analysis was carried out by ICP-MS. The maximum concentrations of these metals were 314.15, 95.88, and 48.36 μg l-1 for Fe, Al and Mn, respectively. The samples with maximum of elements concentration were obtained from after-pour of zovb-e-ahan wastewater, Falavarjan and pole Ghadir stations. The concentration of heavy metals in different stations of this river was different. The analysis shows the critical points of the river and also shows the points that continuous control should be done.